Epiretinal Membrane Impairs the Inner Retinal Layer in a Traction Force-Dependent Manner - Yuki Kanzaki, MD, PhD; Ryo Matoba, MD, PhD; Shuhei Kimura, MD, PhD; Mio M. Hosokawa, MD, PhD; Yusuke Shiode, MD, PhD; Shinichiro Doi, MD, PhD; Tetsuro Morita, MD; Sayumi Kanzaki, MD; Ippei Takasu, MD, PhD; Atsuhiro Tanikawa, MD, PhD; Yuki Morizane, MD, PhD (Ophthalmology Science, 2023)
Purpose: To investigate the relationship between retinal traction force and impairment of the inner retinal layer in patients with epiretinal membrane (ERM). Design: Nonrandomized, retrospective consecutive case series. Participants: Two hundred nine eyes of 201 patients with idiopathic ERM who underwent vitrectomy for idiopathic ERM were enrolled. Methods: Retinal folds caused by ERM were visualized using en face OCT, and the maximum depth of retinal folds within the parafovea (MDRF) was measured. Focal macular electroretinogram (ERG) was used to measure the amplitude and implicit time of each component for the ERM eyes and the normal fellow eyes. B-scan OCT images were used to measure the thicknesses of the inner nuclear layer (INL) and outer nuclear layer (ONL) + outer plexiform layer (OPL). Expression of α-smooth muscle actin (α-SMA) in surgically removed ERM specimens was quantified by reverse-transcription polymerase chain reaction. Main Outcome Measures: We analyzed the relationship between MDRF and the relative amplitudes of focal macular ERG (affected eye/fellow eye), the relationships between MDRF and the mean INL thickness and ONL+OPL thickness, comparison of INL thickness and ONL+OPL thickness for each area when cases were classified according to MDRF localization in the ETDRS chart, and the relationship between MDRF and the relative expression of α-SMA in the ERM specimens. Results: The MDRF significantly correlated with the relative amplitudes (affected eye/fellow eye) of b-waves and oscillatory potentials (r = −0.657, P = 0.015; r = −0.569, P = 0.042, respectively) and the mean INL thickness and ONL+OPL thickness (r = 0.604, P < 0.001; r = 0.210, P = 0.007, respectively). However, only the INL thickness progression rate was significantly correlated with the MDRF progression rate (r = 0.770, P < 0.001). On case stratification by localization of MDRF based on the ETDRS chart, in regions other than temporal regions, the INL thickness was significantly greater in regions with MDRF than in other regions. The MDRF significantly correlated with α-SMA expression in the ERM specimens (r = 0.555, P = 0.009). Conclusions: The findings suggest that ERM impairs the inner retinal layer in a traction force-dependent manner. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article.